Phenomenon of the Paying Zakat Fitrah Twice in Madura: an Economic Fiqh Study - Laili, Mahiratul; Sultoni, Mohammad Hamim; Fadllan, Fadllan (Universitas Islam Negeri Sunan Ampel Sunan Ampel, 2025)
This study explores the social phenomenon of paying zakat fitrah twice a year, especially among children from divorced families. The study was conducted in Sumenep Regency, Madura. The main issue addressed is the legal validity of double zakat fitrah payments according to the perspectives of Islamic jurists specialising in economic fiqh The research method employed was a literature review using a descriptive-analytical approach to both classical and contemporary literature. The researcher examined the views of the four main schools of Islamic jurisprudence as well as Yusuf alQaradawi and Wahbah Zuhaili. Data was collected through interviews with residents of Gersik Putih Village to understand the social phenomenon. The research findings indicate that all fiqh schools agree that zakat fitrah is only obligatory to be paid once a year. If zakat is paid more than once on behalf of one individual, the second payment is considered as charity. The phenomenon of double zakat fitrah for children from divorced families is caused by three main reasons: lack of community understanding of zakat law; parents' desire to contribute equally without clear coordination; and lack of socialisation. This study recommends the importance of education on zakat law and strengthening the role of religious leaders in socialising fiqh zakat to the community.